2012
DOI: 10.1523/jneurosci.4556-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Order Memory Assessed during Spatiotemporal Navigation As a Behavioral Cognitive Marker for Differential Alzheimer's Disease Diagnosis

Abstract: Episodic memory impairment is a hallmark for early diagnosis of Alzheimer's disease. Most actual tests used to diagnose Alzheimer's disease do not assess the spatiotemporal properties of episodic memory and lead to false-positive or -negative diagnosis. We used a newly developed, nonverbal navigation test for Human, based on the objective experimental testing of a spatiotemporal experience, to differentially Alzheimer's disease at the mild stage (N ϭ 16 patients) from frontotemporal lobar degeneration (N ϭ 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 66 publications
3
81
0
3
Order By: Relevance
“…Behavioral interventions that minimize temporal interference and structure daily living tasks into repetitive, fixed sequences may improve memory and perhaps could increase functional independence in older adults. In addition, a recent study reports that impaired temporal order memory may be a selective behavioral marker of Alzheimer's disease (Bellassen et al 2012). Therefore, …”
mentioning
confidence: 99%
“…Behavioral interventions that minimize temporal interference and structure daily living tasks into repetitive, fixed sequences may improve memory and perhaps could increase functional independence in older adults. In addition, a recent study reports that impaired temporal order memory may be a selective behavioral marker of Alzheimer's disease (Bellassen et al 2012). Therefore, …”
mentioning
confidence: 99%
“…In addition, temporal order memory tests may be useful in other age-related neurodegenerative diseases. For example, recent studies have found that temporal order memory is impaired in older adults with mild cognitive impairment (Gillis et al, 2013) and these impairments might be a selective behavioral marker of Alzheimer’s disease (AD; Bellassen et al, 2012). Although future studies are needed to examine the incremental and ecological validity of temporal order memory tasks relative to standard neuropsychological tests, the findings of the current and recent studies suggest that cognitive evaluations in older adults with PD and suspected AD may be improved by the addition of temporal order memory measures, particularly tasks that manipulate the level of temporal interference.…”
Section: Discussionmentioning
confidence: 99%
“…Topographical orientation is one of the abilities mostly affected in normal and pathological aging. Indeed, during normal aging there is a clear trend toward impairment of temporal memory, evaluated overall by sequential navigation information and route tracing [34]. Therefore, it is note worthy that in normal aging a differentiation emerges in the ability to generate a building versus the ability to generate a common object.…”
Section: Discussionmentioning
confidence: 99%